Substrate‐size choice in European eel (Anguilla anguilla) elvers is not altered by piscivore chemical cues. Issue 6 (23rd April 2020) - Nilsson, P. Anders; Pettersson, Ivi J.; Tamario, Carl; Degerman, Erik; Elghagen, Jonas; Watz, Johan; Calles, Olle
Abstract: The European eel Anguilla anguilla Linnaeus 1758 is critically endangered with recruitment estimated at 5–10% of historical levels. Enhancing survival of recruits is pivotal for conservation, and restoration should consider habitat choice of elvers ascending river systems. We experimentally show that newly ascended elvers choose small pebble habitat over finer and larger substrates, regardless of the presence or absence of piscivore chemical cues, indicating no predator‐induced change in substrate choice. Enriching habitats with this substrate fraction should enhance eel recruitment as well as biodiversity at large.